Competence-based assessment in higher music education: faculty perceptions in the Valencian Community - Escorihuela, Guillem; Martínez-Bayona, Tíscar; Marzal, Lluís (Frontiers in Education, 2025)
Competency-based assessment has become a central focus in Higher Artistic Education (HAE) in Spain, yet its practical implementation in music conservatories remains underexplored. This study examines how teachers in Higher Conservatories of Music in the Valencian Community interpret and apply the evaluation principles outlined in Article 1, Chapter IV, of Decree 48/2011. An online questionnaire, specifically designed for this research, was completed by 39 teachers from various specializations. The instrument combined Likert-scale items assessing the adequacy of current systems for evaluating general competencies with multiple-choice questions on methodologies, perceived challenges, and perceptions of fairness, professional readiness, and improvement over traditional models. Data were analyzed using descriptive statistics, visualizations, and chi-square tests to explore relationships among key perception variables. Results indicate that while certain competencies are perceived as adequately assessed, others present significant challenges, particularly in aligning evaluation practices with professional preparation requirements. Perceptions of fairness are ambivalent, with many respondents selecting “partially” or “not sure,” and a significant proportion expressing doubts about the system’s capacity to fully prepare students for professional life. Competency-based assessment is viewed as an improvement over traditional models, but with important limitations. These findings underscore the need for targeted professional development and clearer institutional guidelines to bridge the gap between regulatory frameworks and educational practice.